Soil Characteristics of Settlements in Sukadono Hamlet, Helvetia District, Deli Serdang Regency - Muhammad Azran Bin Azmi; Yoan Carolina Panggabean; Yunilda Andriyani; Bambang Prayugo (Sumatera Medical Journal, 2023)
Background: Soil is where humans can do an abundance of activities. Soil can be contaminated by various factors. Soil is also a medium of development, storage and transmission of several types of worms, commonly referred to as Soil-Transmitted Helminths (STH). Objective: The purpose of this study was to find out the characteristics of residential land in the Sukadono Hamlet Helvetia District Deli Serdang. Methods: The sample in this study was 72 soils taken from the front, back left or right of the house. The soil is measured in temperature, humidity, pH value and is checked using a Digital Soil Analyzer. Results: The results showed that most of the soil characteristics in Sukadono Hamlet Helvetia District Deli Serdang were abnormal. The STH examination results also showed that (45.8%) of the 72 soil samples examined positively contained STH. Hookworms were found in (32.9%) soil samples, Ascaris lumbricoides species in (5.3%) soil samples, Strongyloides stercoralis species were found positive in (7.9%) soil samples and a mixture of STH is present in 2 (3.9%) soil samples. Conclusion: The resident soil in research areas had been contaminated by Soil Transmitted Helminths.